THE DEVELOPMENT OF LEARNING MEDIA STATISTICS E-MODUL BASED ON EDMODO WITH REALISTIC APPROACH ORIENTED HOTS FOR GRADE XII STUDENTS OF SMK - Lina Anggraeni; Suparman Suparman (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2018)
Insufficient teaching media cause a lack of students' interests in mathematics. Moreover, they have difficulty to understand more about statistics. Therefore, we need a teaching media for Statistics E-Modul. This research is aimed to develop teaching media, especially Statistics E-module for grade XII students of vocational high school (SMK). Furthermore, it is also aimed to know how feasible this E-module from a financial point of view and how good of students' responses to this media.  The type of this research is development research. It uses research and development. They are elaborated in some stages, such a problem identification, data collection, product, and good design, product revision, trial usage, product revision, and mass production. The subject of this research is SMK N 1 Sanden and SMK 1 Muhammadiyah Bambanglipuro. Meanwhile, the object of the study is a statistics e-module based on Edmodo with a realistic approach oriented HOTS (Higher Order Thinking Skill) for grade XII students of vocational high school. There are two types of data. Those are qualitative and quantitative. The data collection uses interviews and questionnaires, which will be done before product development, is done. The instrument of the research is the guidelines of interview and questionnaire to rate the E-Module. The data analysis technique is a quantitative analysis that will be changed into qualitative analysis using a Likert scale.  The research result showed that the result of scoring instrument from the expert with the average score 124.7 is in the level good. The result of the research showed that the result of the scoring instrument fro the expert with the average score 91.7 is in the level very good. Moreover, the instrument of students’ responses with the average score 85.53 is in the level very good. Based on the scoring result from the expert, media expert, students' responses to the development of teaching media statistics e-module based on Edmodo with a realistic approach oriented HOTS (Higher Order Thinking Skill)  for grade XII students of vocational high school is feasible to apply in the learning process.